Stall-Induced Vibrations of the AVATAR Rotor Blade. Issue 4 (September 2016) - Stettner, M; Reijerkerk, M J; Lünenschloß, A; Riziotis, V; Croce, A; Sartori, L; Riva, R; Peeringa, J M
Abstract: In the course of the AVATAR project, partner predictions for key load components in storm/idle conditions separated in two groups. One group showed large loading due to edgewise instability, the other group damped edgewise oscillation and lower load levels. To identify the cause for this separation, the impact of structural and aerodynamic modeling options on damping of stall-induced vibrations is investigated for two simplified operating conditions of a single AVATAR blade. The choice of the dynamic stall model is found to be the primary driver, and is therefore most likely also the reason for previously observed differences in AVATAR storm load predictions. Differences in structural dynamics, mode shapes, structural and dynamic twist, as well as wake model are only secondary in terms of impact on damping. Resolution suffered from failure of system identification methods to extract reliable damping values from various non-linear response simulations.